(3GdefKhQ hGdefXhes - (3GHf CHj WGgQ WjahQ , CMeO Hf WjahQ CHj WGgQ GdNQGSGfj, CHh GdaVd,J (B280 (3g` s
(3ChdgG (B:s
(3bGd CHhGdaVd gPG cJGH HdGZGJ GdfSGA s
(3BNQgG (B:s
(3fLR cJGH GdaUhd hGdQSGFd hgh BNQ cJGH GdefKhQ hGdefXhe s
(3HgG fXGe GdJYbjHIs
(3LRA efg jJVef KdGKI CLRGA GdMGOi YTQs
(3GdKGfi YTQ hGdKGdK YTQ hGdcGed efg ai CQHYI YTQ LRAkGs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs